READING AL-BURHÂN FI USHÛL AL-FIQH BY AL-JUWAINI: A STUDY OF TUBE BABY CASE RESOLUTION - Daruhadi, Gagah (Ridwan Institute, 2024)
Islamic jurisprudence has been widely used in addressing modern bioethical issues, such as in vitro fertilization (IVF). However, few studies have explored the application of Tafsir Ahkam in modern medical ethics. This research presents a novel approach by integrating classical Islamic judicious principles with modern medical ethical issues. The research is conducted through literature review on classical and contemporary texts related to ushul fiqh and fatwas concerning IVF in Indonesia. The aspects explored include Imam Al-Juwayni's thoughts in his work